Investigation of deep electronic levels in n‐type and p‐type 3C‐SiC using photoluminescence - Wilhelm, Martin; Syväjärvi, Mikael; Wellmann, Peter (Advanced Materials Proceedings, 2017)
Among the various SiC polytypes, cubic 3C‐SiC is much more difficult to grow in high crystalline quality than the commercially introduced hexagonal 6H‐SiC and 4H‐SiC counterparts. Besides some benefits of 3C‐SiC for transistor applications related to a greater electron mobility and a lower metal‐oxide‐semiconductor interface trap density compared to 4H‐SiC, new potential optoelectronic applications have been introduced very recently. Boron doped 3C‐SiC may act as an ideal candidate for an intermediate band (IB) solar cell material. Aluminum doped p‐type 3C‐SiC could lead to the development of efficient optoelectrochemical water splitting cells. Finally, 3C‐SiC with its various intrinsic point defects has been considered as a suitable candidate for future spintronic‐applications. All these applications will critically depend on further understanding defect behaviour on atomic level. In our study we investigated free standing n‐type and p‐type 3C‐SiC material grown in our lab. Temperature dependent photoluminescence measurements revealed the presence of carbon vacancy related VC and VC-CSi defect transitions in the p‐type materials but not in the n‐type materials. This observation present in as grown 3C-SiC is believed to have significant impact on the optoelectronic applications.
Keywords: 3C-SiC; doping; p-type; defects; carbon vacancy

Optimization of growth parameters for growth of high quality heteroepitaxial 3C-SiC films at 1200 degrees C - Wilhelm, Martin; Rieth, Marcel; Brandl, Marco; Wibowo, Rachmat Adhi; Hock, Rainer; Wellmann, Peter (Thin Solid Films, 2015)
In order to reduce the residual stress caused by the mismatch of thermal expansion coefficients of 3C-SiC layers grown on Si after cooling down to room temperature, the growth temperature was reduced from usually above 1300 degrees C to 1200 degrees C. Epitaxial layers with high crystalline quality were grown on 1 x 1 cm(2) (100) Si substrates. The layers were evaluated by means of x-ray diffraction (XRD), Raman measurements, scanning electron microscopy and atomic force microscopy. Full width at half maximum values of 0.19 degrees for XRD rocking curve measurements of the (200) 3C-SiC peak were achieved, indicating high crystalline quality of the layers and epitaxial growth. For optimized growth at 1200 degrees C a high C/Si-ratio, on-axis substrates and a layer thickness of over 1 mu m are necessary. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Cubic silicon carbide; Heteroepitaxy; X-ray diffraction; Raman spectroscopy

Photoluminescence topography of fluorescent SiC and its corresponding source crystals - Wilhelm, Martin; Kaiser, Michl; Jokubavicius, Valdas; Syväjärvi, Mikael; Ou, Yiyu; Ou, Haiyan; Wellmann, Peter (Materials Science Forum, 2013)
The preparation and application of co-doped polycrystalline SiC as source in sublimation growth of fluorescent layers is a complex topic. Photoluminescence topographies of luminescent 6H-SiC layers and their corresponding source crystals have been studied in order to investigate the dependence of the epitaxial growth on the source material. It is shown that the homogeneity concerning the dopant incorporation and the layer luminescence intensity does not depend on the characteristics of the PVT grown source material. Therefore co-doped polycrystalline SiC is a promising source material in fast sublimation growth of luminescent 6H-Si
Keywords: luminescent SiC; 6H-SiC; epitaxy; photoluminescence topography

Single Domain 3C-SiC Growth on Off-Oriented 4H-SiC Substrates - Jokubavicius, Valdas; Yazdi, Gholam R.; Liljedahl, Rickard; Ivanov, Ivan G.; Sun, Jianwu; Liu, Xinyu; Schuh, Philipp; Wilhelm, Martin; Wellmann, Peter; Yakimova, Rositsa; Syväjärvi, Mikael (Crystal Growth & Design, 2015)
We investigated the formation of structural defects in thick (similar to 1 mm) cubic silicon carbide (3C-SiC) layers grown on off-oriented 4H-SiC substrates via a lateral enlargement mechanism using different growth conditions. A two-step growth process based on this technique was developed, which provides a trade-off between the growth rate and the number of defects in the 3C-SiC layers. Moreover, we demonstrated that the two-step growth process combined with a geometrically controlled lateral enlargement mechanism allows the formation of a single 3C-SiC domain which enlarges and completely covers the substrate surface. High crystalline quality of the grown 3C-SiC layers is confirmed using high resolution X-ray diffraction and low temperature photoluminescence measurements.
Keywords: 3C-SiC; lateral enlargement; sublimation epitaxy; geometrical control

Sublimation growth of bulk 3C-SiC using 3C-SiC-on-Si (1 0 0) seeding layers - Schuh, Philipp; Schöler, Michael; Wilhelm, Martin; Syväjärvi, Mikael; Litrico, G.; La Via, F.; Mauceri, M.; Wellmann, Peter (Journal of Crystal Growth, 2017)
We have developed a transfer process of 3C-SiC-on-Si (1 0 0) seeding layers grown by chemical vapor deposition onto a poly- or single-crystalline SiC carrier. Applying subsequent sublimation growth of SiC in [1 0 0] direction resulting in large area crystals (up to ≈11 cm2) with a thickness of up to approximately 850 <g fill="currentColor" stroke="currentColor" stroke-width="0" transform="matrix(1 0 0 -1 0 0)"><g><g><use xlink:href="http://www.sciencedirect.com/science/article/pii/S0022024817305377?via%3Dihub#MJMATHI-3BC"></use></g></g></g> m. Raman spectroscopy, Laue X-ray diffraction and electron-backscattering-diffraction revealed a high material quality in terms of single-crystallinity without secondary polytype inclusions, antiphase boundaries or double positioning grain boundaries. Defects in the bulk grown 3C-SiC, like protrusions with surrounding stressed areas, stem from the epitaxial seeding layer. The presented concept using 3C-SiC-on-Si seeding layers reveals a path for the growth of bulk 3C-SiC crystals.
Keywords: 3C-SiC; Quasi-bulk; Sublimation epitaxy; DPB free; Single crystalline; Stacking faults

Towards the growth of SiGeC epitaxial layers for the application in Si solar cells - Wilhelm, Martin; Beck, Felix; Wellmann, Peter (Energy Procedia, 2015)
For the improvement of today's well established silicon solar cells a further significant increase in light conversion efficiency needs the consideration of multi junction aspects. In this context 3C-SiC with a bandgap of 2.3 eV has already been discussed in the past. However, an ideal bandgap match within a silicon tandem cell (Eg(Si) = 1.1 eV) requires a lower bandgap of 1.8 eV which may be reached by the incorporation of Ge in the 3C-SiC lattice. In this work we report on the growth of Si-Ge-C hetero-epitaxial layers on silicon in a MOCVD reactor. A major obstacle in realizing a high Ge-content in the cubic 3C-SiC lattice is the strong trend towards segregation and phase separation in the ternary system. In terms of the atomic diameter, Ge should be more likely to substitute Si in the SiC lattice. However, concerning the excess energy the bond between Ge and C is not supposed to be stable. We will present several growth runs at different precursor flow-rates and different temperatures in the range of 1090 °C - 1330 °C and discuss the appearance of a SiGe phase. In order to detect the different bonds in the layers, especially Ge-C bonds, the samples were investigated by means of Raman-spectroscopy and x-ray diffraction. The Ge concentration was investigated by EDX measurements. No proof for the formation of Ge-C was found so far.
Keywords: 3C-SiC; SiGeC; Epitaxy; Raman; X-Ray diffraction